Work, eat and sleep: towards a healthy ageing at work program offshore - Riethmeister, Vanessa (BMC Public Health, 2016)
BACKGROUND: Health management tools need to be developed to foster healthy ageing at work and sustain employability of ageing work-forces. The objectives of this study were to 1) perform a needs assessment to identify the needs of offshore workers in the Dutch Continental Shelf with regard to healthy ageing at work and 2) to define suitable program objectives for a future healthy ageing at work program in the offshore working population. METHODS: A mixed methods design was used applying an intervention mapping procedure. Qualitative data were gathered in N = 19 semi-structured interviews and six focus-group sessions (N = 49). Qualitative data were used to develop a questionnaire, which was administered among N = 450 offshore workers. Subgroup analyses were performed to investigate age-related differences relating to health status and work-related factors. RESULTS: The importance of good working environments, food, as well as sleep/fatigue management was identified by the qualitative data analysis. A total of 260 offshore workers completed the questionnaire. Significant differences in work ability were found between offshore workers aged <45 and 45–54 years (mean 8.63 vs. 8.19; p = 0.005) and offshore workers aged <45 and >55 years (mean 8.63 vs. 8.22; p = 0.028). Offshore workers had a high BMI (M = 27.06, SD = 3.67), with 46 % classified as overweight (BMI 25–30) and 21 % classified as obese (BMI >30). A significant difference in BMI was found between offshore workers aged <45 and ≥55 years (mean 26.3 vs. 28.6; p <0.001). In total, 73 % of offshore workers reported prolonged fatigue. A significant difference in fatigue scores was found between offshore workers aged <45 and ≥55 years (mean 36.0 vs. 37.6; p = 0.024). Further, a “dip” was reported by 41 % of offshore workers. Dips were mainly experienced at day 10 or 11 (60 %), with 45 % experiencing the dip both as physical and mental fatigue, whereas 39 % experienced the dip as only mental fatigue. CONCLUSIONS: Both qualitative and quantitative analyses identified work, food and sleep/fatigue management as most important program objectives for a healthy ageing at work and sustainable employability program offshore. Future studies should investigate possible causes of dip occurrences and high fatigue scores to identify suitable interventions. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s12889-016-2807-5) contains supplementary material, which is available to authorized users.